General Norton de Matos (1867-1955): aspectos maiores de um perfil histórico-biográfico - o militar, o colonialista e o democrata - Silva, Armando B. Malheiro da (Africana Studia, 2020)
ln spite of have been a public figure of great prestige during the legality of the I Portuguese Republic (1910-1926) as General Governar of Angola, Minister of the Colonies and of the War, responsible for the preparation of the Portuguese Expeditionary Regiment in the Great War (1914-1918), High Comissary in Angola and Ambassador in London, and in the Oposition to the New State until the end ofhis life in 1955, the General José Ribeiro Mendes Ribeiro Norton de Matos has not deserved of the portuguese community of contemporary historians and even of the colonial history experts, particulary about Angola, the deep and systematic investigation that should be made. This article compact only the results of a research in progress and an editorial project assumed by the Center of Interdisciplinary Studies of 20th Century of the University of Coimbra through the protocol signed with the General Heirs (owners of his important Personal and Familiar Archives and Library) and with the Ponte de Lima Municipal Council), but at the sarne time it perfils itself as a encouragement that we wish to be solid and serious, for an exaustive research program around this colonialist, republican and democratic figure and around the great issues that cross his life trajectory and by his era.